PENERAPAN MANAJEMEN KINERJ A PADA PT. (PERSERO) ANGKASA PURA I BANDAR UDARA SAM RATULANGI MANADO - Rahmat Sabuhari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
Modern enterprises , putting the company 's performance should reallybe measured, giving rise to test rank - performance measurement ,therefore need human resource management within the company so thatproductivity can be increased , which in turn is expected by the companyobjectives can be achieved . It is called the performance management. Performance management should be able to ascertain the level ofsuccess or failure of the company's activities. This research is about how the implementation of performance management at PT . ( Persero ) Angkasa Pura I airport Sam Ratulangi Manado . Therefore the main objective of this study was to determine the extent to which the implementation of performance management . The data used is primary data and secondary data . Primary data were obtained by conducting in-depth interviews with 4 people informant fromthe corporate office . The analytical method used was a qualitative studyusing a general inductive approach . It is intended to assist theunderstanding of the meaning of the data is complicated by thedevelopment of the themes outlined in the raw data , and then drawn aconclusion of the interview. The findings of the research showed that employee initiative can be implemented , the role is poorly understood , dependence on superiors quite high , reports are often late , and a leadership style that is applied very supportive of employee performance . Fore expected to socializeleadership to employees in order to understand the implementation ofperformance management in his company well.